Add-On Effect of Honeysuckle in the Treatment of Coronavirus Disease 2019: A Systematic Review and Meta-Analysis - Du, Xu-Qin; Shi, Li-Peng; Cao, Wen-Fu; Chen, Zhi-Wei; Zuo, Biao; Hu, Jin-Yuan (Frontiers in Pharmacology, 2021)
Background: The outbreak of coronavirus disease 2019 (COVID-19) has rapidly spread to become a global emergency since December 2019. Chinese herbal medicine (CHM) plays an important role in the treatment of COVID-19. Chinese herbal medicine honeysuckle is an extremely used traditional edible and medicinal herb. Many trials suggest that honeysuckle have obtained good curative effect for COVID-19; however, no systematic evaluation on the clinical efficacy of honeysuckle in the treatment of COVID-19 is reported. This study aimed to evaluate the efficacy and safety of Chinese herbal medicine honeysuckle in the treatment of COVID-19. Methods: Seven electronic databases (PubMed, EMBASE, Cochrane Library, China National Knowledge Infrastructure, China Science and Technology Journal Database, Wanfang Database, and China Biology Medicine) were searched to identify randomized controlled trials (RCTs) of honeysuckle for adult patients (aged≥18 years) with COVID-19. The Cochrane Risk of Bias Tool was applied to assess the methodological quality of trials. Review Manager 5.3 software was used for data analysis. Results: Overall, nine RCTs about involving 1286 patients were enrolled. Our meta-analyses found that combination therapy of honeysuckle and conventional therapy was more effective than conventional therapy alone in lung CT [RR=1.24, 95%CI (1.12, 1.37), P＜0.0001], clinical cure rate [RR=1.21, 95%CI (1.12, 1.31), P＜0.00001], and rate of conversion to severe cases [RR=0.50, 95%CI (0.33, 0.76), P=0.001]. Besides, combination therapy can improve symptom score of fever, cough reduction rate, symptom score of cough, and inflammatory biomarkers (white blood cell count, C-reactive protein) (P < 0.05). Conclusions: Honeysuckle combined with conventional therapy may be beneficial for the treatment of COVID-19 in improving lung CT, clinical cure rate, clinical symptoms, and laboratory indicators, and reducing rate of conversion to severe cases. Besides, combination therapy did not increase adverse drug events. More high-quality RCTs are needed in the future.